The Deceased Child and his Configuration as Little Angel. Northern Argentina and Southern Paraguay - Bondar, César Iván (2022)
We present the results of the research on deceased children and their configuration as little angel (delimiting cases tospontaneous or natural abortions, children who died before delivery or shortly after birth) among the population of theCatholic faith, in the North of the Argentine Republic and the South of Paraguay. The ethnographic method, in-depth interviewsand observations with different degrees of participation have been prioritized; the field work has been carried out between2010 and 2018. We focus on the analysis on the ways of understanding, explaining and experiencing the death of the casesmentioned. We realize a particular way of constructing death in close connection to the emic category of little angel. In thetypes of death indicated, the post-mortem destiny will be the Third Heaven. The little angel will be given a special space in theuniverse of the dead. Being protector of the living, he is empowered to make the mediation relationships between the humanand the sacred; namely: between men and God.